(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background The nutrient foramen is the external opening in each bone, which has a particular position and number in its diaphysis. As one of the most common bones used in bone grafts, vascularized bone microsurgery, and mandibular reconstruction, it is important to have a full understanding of the position, number, direction, and variation of the fibula's nutrient foramina. Aim and objectives of the study: To determine the position of nutrient artery foramina in the fibula, as well as their size and direction. Methods and Materials: In the present study, a total of 120 dry fibulae bones (50 on the right and 70 on the left) were examined. The number, position, size, and direction of nutrient foramina were recorded in a preprinted proforma. The range, mean, and standard deviation of the foraminal index (FI), as well as its calculation, were determined. Results: A total of 114 nutrient foramina were found out of 120 dry fibula bones examined. There were 105 dominant foramina and 09 secondary foramina among the 114 nutrient foramina. Foramina were missing on four right-sided bones and two left-sided bones. Most of the foramina were located on the posterior surface. The majority of the foramina on the right side were located between the medial crest and the posterior border on the posterior surface. The majority of the foramina on the left side were found between the interosseous border and the medial crest on the posterior surface. Conclusion: A thorough anatomical knowledge of the nutrient foramen is useful in planning the vascularized fibular graft. Hence, the result of this study will provide detailed data about the number, position, and direction of nutrient artery foramina in the fibula for the successful outcome of various orthopaedic and plastic reconstructive surgeries.